(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the use of information technologies and the modernization of accounting software during the transition of business entities to IFRS (International Financial Reporting Standards). It highlights automated accounting processes, the need to adapt software to international standards, an analysis of advanced foreign practices, and challenges emerging in Uzbekistan. The study also discusses the prospects of developing accounting processes through digital technologies, including artificial intelligence and blockchain